PECULIARITIES OF STUDENTS’ EDUCATIONAL MOTIVA- TION - Коробкіна, Регіна Сергіївна; Невоєнна, Олена Анатоліївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
This article describes the features of the structure of educational motivation of students of 1st and 4 th courses. The study showed that the learning motivation of students is characterized by a fairly high level of cognitive interest, interest in learning, creative self-realization and the desire to become a competent specialist. However, changes in the structure of learning motivation are observed during the training. So for fist-year students there is a high level of interest, the need for self-development, the idealization of the educational process and training, besides, a high orientation towards the external attractiveness and prestige of the chosen profession. While fourth-year students are characterized by a more realistic view of the diffiulties and peculiaritiesof studying in higher education institutions, they are mainly focused on development and self-realization in  professional terms, therefore, they are characterized by a decrease in educational and cognitive motives. Firstyear students act as more active and active in relation to educational and cognitive activity; they rely on their expectations and ideas about the profession they have chosen and about their studies at the university. While fourth-year students are already less reliant on their ideas about the profession, they saw from the inside how the learning process goes, and imagine what their profession will be like. By this time, fourth-year students may refuse the profession chosen four years ago, search for themselves in other specialties, or vice versa, seek and try themselves in professional activities. The results obtained can be a guide to action regarding the formation of such learning conditions that will contribute to the creative development and professional realization of students.